The Indonesia green policy: A realistic shifting into a green energy to boost public welfare - Jonathan Ersten Herawan; Yuvensius Sri Susilo; Matthew Kartawinata; Kholia Kholia (Qualitative Research of Business and Social Sciences, 2024)
This research aims to identify and analyze the challenges and opportunities that Indonesia faces in transitioning from conventional energy to new and renewable energy (EBT). The world's increasingly multipolar and conservative condition certainly requires national vigilance. Indonesia will have difficulty escaping the middle-income trap if the national economy still depends on the global economy. This research uses qualitative descriptive and literature study collection, which is complemented by data from BPS RI, the Ministry of Energy and Mineral Resources of the Republic of Indonesia, and the Ministry of Finance of the Republic of Indonesia for 2012-2022 to map and change the problem of energy dependence as well as provide policy recommendations on national energy security through new and renewable energy. Policy recommendations from this research are divided into three periods: short-term, medium-term, and long-term.